An immunoproteomics approach to identify Leishmania infantum proteins to be applied for the diagnosis of visceral leishmaniasis and human immunodeficiency virus co-infection. Issue 9 (20th August 2020) - Machado, Amanda S.; Ramos, Fernanda F.; Oliveira-da-Silva, João A.; Santos, Thaís T. O.; Tavares, Grasiele S. V.; Costa, Lourena E.; Lage, Daniela P.; Teixeira-Ferreira, André; Perales, Jonas; Fernandes, Ana Paula; Moreira, Ricardo L. F.; Duarte, Mariana C.; et al.
Abstract: The co-infection between visceral leishmaniasis (VL) and human immunodeficiency virus (HIV) has increased in several countries in the world. The current serological tests are not suitable since they present low sensitivity to detect the most of VL/HIV cases, and a more precise diagnosis should be performed. In this context, in the present study, an immunoproteomics approach was performed using Leishmania infantum antigenic extracts and VL, HIV and VL/HIV patients sera, besides healthy subjects samples; aiming to identify antigenic markers for these clinical conditions. Results showed that 43 spots were recognized by antibodies in VL and VL/HIV sera, and 26 proteins were identified by mass spectrometry. Between them, β -tubulin was expressed, purified and tested in ELISA experiments as a proof of concept for validation of our immunoproteomics findings and results showed high sensitivity and specificity values to detect VL and VL/HIV patients. In conclusion, the identified proteins in the present work could be considered as candidates for future studies aiming to improvement of the diagnosis of VL and VL/HIV co-infection.